Preparation and properties of polyamide-6-based thermoplastic laminate composites by a novel in-mold polymerization technique - Dencheva, Nadya Vasileva (2014)
In this work, a method for preparation of polyamide-6 (PA6) based laminates reinforced by glass fiber- (GFL) or polyamide-66 (PA66) textile structures (PL) via reactive injection molding is disclosed. It is based on in-mold anionic polymerization of eps-caprolactam carried out at 165º C in the presence of the respective reinforcements performed in newly developed prototype equipment whose design concept and operation are described. Both composite types were produced for reaction times of 20 min, with conversion degrees of 97–99%. Initial mechanical tests in tension of GFL samples displayed almost twofold increase of the Young’s modulus and stress at break values when compared with the neat anionic PA6. The improvement was proportional to the volume fraction Vf of glass fiber fabric that was varied in the 0.16–0.25 range. A 300% growth of the impact strength was registered in PL composites with Vf of PA66 textile of 0.1. Removing the surface finish of the latter was found to be a factor for improving the adhesion at the matrix–fiber interface. The mechanical behavior of GFL and PL composites was discussed in conjunction with the morphology of the samples studied by optical and electron microscopy and the matrix crystalline structure as revealed by synchrotron X-ray diffraction.